2010
DOI: 10.1002/ijc.25375
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia, methylenetetrahydrofolate reductase c.677C>T polymorphism and risk of cancer: Cross‐sectional and prospective studies and meta‐analyses of 75,000 cases and 93,000 controls

Abstract: Global DNA hypomethylation associates with development of cancer. DNA hypomethylation also associates with hyperhomocysteinemia and MTHFR c.677C>T homozygosity, both of which may associate with increased risk of cancer. We tested the putative association of hyperhomocysteinemia with cancer and the association of the MTHFR c.677TC>T variant with hyperhomocysteinemia and with cancer. We performed a cross-sectional study of 5,949 Danish general population adults, a prospective study of 9,235 Danish general popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 44 publications
4
51
2
1
Order By: Relevance
“…• MTHFR polymorphism genotyping should not be ordered as part of the clinical evaluation for thrombophilia or recurrent pregnancy loss • MTHFR polymorphism genotyping should not be ordered for at-risk family members • A clinical geneticist who serves as a consultant for a patient in whom an MTHFR polymorphism(s) is found should ensure that the patient has received a thorough and appropriate evaluation for his or her symptoms • If the patient is homozygous for the "thermolabile" variant c.665C→T, the geneticist may order a fasting total plasma homocysteine, if not previously ordered, to provide more accurate counseling • MTHFR status does not change the recommendation that women of childbearing age should take the standard dose of folic acid supplementation to reduce the risk of neural tube defects as per the general population guidelines [71][72][73][74][75][76][77] Lack of evidence for MTHFR polymorphism testing | HICKEY et al ACMG PrACtiCe Guidelines recent study suggests that the effect is ameliorated in populations with folate supplementation. 61 There is no known contraindication to taking oral contraceptives.…”
Section: Box 1: Acmg Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…• MTHFR polymorphism genotyping should not be ordered as part of the clinical evaluation for thrombophilia or recurrent pregnancy loss • MTHFR polymorphism genotyping should not be ordered for at-risk family members • A clinical geneticist who serves as a consultant for a patient in whom an MTHFR polymorphism(s) is found should ensure that the patient has received a thorough and appropriate evaluation for his or her symptoms • If the patient is homozygous for the "thermolabile" variant c.665C→T, the geneticist may order a fasting total plasma homocysteine, if not previously ordered, to provide more accurate counseling • MTHFR status does not change the recommendation that women of childbearing age should take the standard dose of folic acid supplementation to reduce the risk of neural tube defects as per the general population guidelines [71][72][73][74][75][76][77] Lack of evidence for MTHFR polymorphism testing | HICKEY et al ACMG PrACtiCe Guidelines recent study suggests that the effect is ameliorated in populations with folate supplementation. 61 There is no known contraindication to taking oral contraceptives.…”
Section: Box 1: Acmg Recommendationsmentioning
confidence: 99%
“…69,70 The overall cancer risk does not appear to be changed. 71 Patients should be counseled that it is important to provide their MTHFR genotype status to any physician who is considering starting them on types of chemotherapy whose activity depends on intracellular concentration of folate (e.g., methotrexate). In individuals who have a known thrombophilia, such as factor V Leiden or prothrombin c.*97G→A, most available studies support the contention that MTHFR genotype status does not alter their thrombotic risk to a clinically significant degree.…”
Section: Box 1: Acmg Recommendationsmentioning
confidence: 99%
“…Studies conducted in China (Qin et al, 2008), Iran (Saberi et al, 2012), Korea (Cui et al, 2010), Mexico (ZunigaNoriega et al, 2007;Galvan-Portillo et al, 2009), Norway (Vollset et al, 2007), and Denmark (Zacho et al, 2011) identified a significant association of the MTHFR C677T polymorphism with gastric cancer. Studies in China, Iran, and Denmark indicated a significantly increased risk of gastric cancer, with ORs ranging from 1.4-2.6 (Qin et al, 2008;Zacho et al, 2011;Saberi et al, 2012). In contrast, several other studies have indicated that MTHFR 677TT significantly protects against gastric cancer (Galvan-Portillo et al, 2009;Cui et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Because the DNA methylation plays a critical role in regulation of gene expression and maintenance of genomic stability, the aberrations in normal methylation patterns have been associated with the development of cancer by impairing the DNA methylation (Cheng et al, 1997). More importantly, the homozygous variant genotype MTHFR 677TT has been associated with risk for many different types of cancer, including colorectal cancer, gastric cancer and breast cancer (Taioli et al, 2009;Dong et al, 2010;Zacho et al, 2011).…”
Section: Discussionmentioning
confidence: 99%